Understanding microbiome dynamics and functional responses during acidogenic fermentation of sucrose and sugarcane vinasse through metatranscriptomic analysis - Mota, Vera T.; Delforno, Tiago P.; Ribeiro, Jaqueline C.; Zaiat, Marcelo; Oliveira, Valéria M. de (Environmental research, 2024)
Improving anaerobic digestion of sugarcane vinasse – a high-strength wastewater from ethanol distillation – is a subject of great interest, in view of the reduction of the pollutants and recovery of methane and valuable metabolites as byproducts. Through metatranscriptomic analysis, this study evaluated the active microbiome and metabolic pathways in a continuous acidogenic reactor: Stage 1S (control): 100% sucrose-based substrate (SBS); Stage 2SV (acclimation): 50% SBS and 50% vinasse; Stage 3V: 100% vinasse. Metatranscriptome obtained from each Stage was subjected to taxonomic and functional annotations. Under SBS feeding, pH dropped to pH 2.7 and biohydrogen production was observed. As vinasse was added, pH increased to 4.1–4.5, resulting in community structure and metabolite changes. In Stage 3V, biohydrogen production ceased, and propionate and acetate prevailed among the volatile fatty acids. Release of homoacetogenesis enzymes by Clostridium ljungdahlii and of uptake hydrogenase (EC 1.12.99.6) by Pectinatus frisingensis were linked to hydrogen consumption in Stages 2SV and 3V. Metabolic pathways of vinasse compounds, such as carbohydrates, malate, oxalate, glycerol, sulfate and phenol, were investigated in detail. In pyruvate metabolism, gene transcripts of oadA (oxaloacetate decarboxylase) and mdh (malate dehydrogenase), were upregulated in Stage 3V, being mostly attributed to P. frisingensis. Acetate formation from vinasse degradation was mainly attributed to Megasphaera and Clostridium, and propionate formation to P. frisingensis. Glycerol removal from vinasse exceeded 99%, and gene transcripts encoding for glpF (glycerol uptake facilitator protein), glpK (glycerol kinase) and glpABC (glycerol-3-phosphate dehydrogenase) were expressed mostly by Pectinatus and Prevotella. mRNA profiling showed that active bacteria and gene expression greatly changed when vinasse replaced sucrose, and Pectinatus was the main active bacterium degrading the searched compounds from vinasse. The identification of the main metabolic routes and the associated microorganisms achieved in this work contributes with valuable information to support further optimization of fermentation towards the desired metabolites. [Display omitted] •A continuous acidogenic bioreactor was fed with sucrose followed by vinasse.•mRNA profiling revealed microbial functions and metabolic pathways in each stage.•Bacteria involved in biohydrogen production and consumption were unveiled.•Pectinatus frisingiensis was the most active microorganism under vinasse feeding.•Specific metabolic routes of vinasse compounds degradation were reconstructed.